Perilaku Mahasiswa dalam Pencegahan Obesitas - Ariyanto Ariyanto; Tina Yuli Fatmawati; Filius Chandra; Nel Efni (Jurnal Akademika Baiturrahim Jambi, 2023)
Basic Health Research (Riskesdas) explains obesity in adolescents aged 16-18 years with the (BMI/U) category of 4.0%, an increase from 2013 which was 1.6%. In West Kalimantan, the prevalence of obesity in adolescents aged 16-18 years increased from only 1.0% in 2013 to 3.4% in 2018. Meanwhile, the prevalence of obesity in adolescents aged 16-18 years in Pontianak city also increased from 2013, which was only 0. .5% to 1.75% in 2018. The teenagers are experiencing obesity because their lifestyles are much different, judging by their habit of consuming fast food on the grounds that they follow trends, are practical and taste better. The purpose of this study was to determine student behavior in obesity prevention. The type of research is a descriptive study that aims to determine obesity prevention behavior in STIKes Baiturrahim Jambi students. The research was conducted in February -March 2022. The sample used was 239 people using the proportional sampling technique. The research instrument used a questionnaire, then analyzed univariat. The results showed that the behavior of respondents in the effort to prevent obesity was mostly good, 123 respondents (51.1%). It is suggested to respondents to apply healthy living behaviors in everyday